FORMULATION SALEP FENNEL LEAVES EXTRAC (Feoniculum vulgare Mill) WITH SALEP HIDROKARBON BASE VARIATION (VASELIN ALBUM) AND WATER BASE (PEG 6000) ON Staphylococcus aureus - Riris Nurul Hidayah; Beta Ria Erika Marita Dellima; Mitta Aninjaya (STIKES DUTAGAMA KLATEN, 2017)
Background: Fennel leaves (Feoniculum vulgare Mill) has potential as a medicine. The content of polyphenols, saponins, essential oils, and flavonoids found in the leaves show antibacterial effects. Fennel leaf extract is more perfect when formulated in ointment form. The use of ointment may allow direct contact with the skin. Objective: The objective of this research was to know the antibacterial activity and physical characteristic of fennel leaves extract (Feoniculum vulgare Mill) as inhibitor of Staphylococcus aureus. Research Method: This research is an experimental research by using One Group Pretest Posttest method. Fennel leaf extract (Feoniculum vulgare Mill) was obtained by maceration for 5 days. Furthermore fennel leaf extract identified active compounds contained therein. Then fennel leaf extract at concentrations of 20%, 25%, 30%, 35%, and 40% were tested for antibacterial activity of Staphylococcus aureus. Fennel leaf extract of 40% concentration is formulated in an ointment preparation with a hydrocarbon base (vaseline album) and water soluble base (PEG 6000). Testing of antibacterial activity using Staphylococcus aureus and physical properties of ointment. Testing of antibacterial activity using Staphylococcus aureus with agar diffusion method with sunuran technique, while for Tests physical properties of ointment include organoleptic test, homogeneity test, scattering, adhesion, power protection test, pH test. The data obtained were analyzed by Anova test statistic and Kruskal Wallis test. Result: The result of identification of active compound of fennel leaf extract have flavonoids, polyphenols, saponins. The base salt of hydrocarbon (vaseline album) and water soluble base (PEG 6000) showed that the spread of both ointment base did not show any significant difference and adhesion showed significant difference. The antibacterial activity of the hydrocarbon base ointment (vaseline album) and the water soluble base (PEG 6000) has a significant difference. Conclusion: The base used in this study has an effect on the physical quality of fennel leaf extract. This is seen from the scattering power value and the attachment power of both formulations. An ointment preparation with a hydrocarbon base (vaseline album) and a water soluble base (PEG 6000) affects the effectiveness of antibacterial ointment.